Aplikasi Regresi Logistik Biner Pada Kejadian Putus Sekolah Pekerja Anak Di Pulau Sulawesi - Rosmini, Nazlia; Istiana, Nofita (Jurnal MSA (Matematika dan Statistika serta Aplikasinya), 2025)
Children are the future generation of the nation and play a vital role in national development. However, those from low-income families are often forced into child labor, which can hinder their educational attainment. Balancing work and school responsibilities frequently leads to school dropouts among child laborers. Sulawesi Island is one of the regions in Indonesia with a notably high prevalence of child labor. This study found that 16.39% of child laborers on Sulawesi Island dropped out of school. Using logistic regression analysis on data from the March 2022 National Socio-Economic Survey (Susenas), the study identified that a child's gender, age, poverty status, and the education level of the head of the household significantly influence the incidence of school dropout among child laborers.